Differential Regulation of Gene Expression of Alveolar Epithelial Cell Markers in Human Lung Adenocarcinoma-Derived A549 Clones. (17th June 2015) - Kondo, Hiroshi; Miyoshi, Keiko; Sakiyama, Shoji; Tangoku, Akira; Noma, Takafumi
Abstract : Stem cell therapy appears to be promising for restoring damaged or irreparable lung tissue. However, establishing a simple and reproducible protocol for preparing lung progenitor populations is difficult because the molecular basis for alveolar epithelial cell differentiation is not fully understood. We investigated an in vitro system to analyze the regulatory mechanisms of alveolus-specific gene expression using a human alveolar epithelial type II (ATII) cell line, A549. After cloning A549 subpopulations, each clone was classified into five groups according to cell morphology and marker gene expression. Two clones (B7 and H12) were further analyzed. Under serum-free culture conditions, surfactant protein C ( SPC ), an ATII marker, was upregulated in both H12 and B7. Aquaporin 5 ( AQP5 ), an ATI marker, was upregulated in H12 and significantly induced in B7. When the RAS/MAPK pathway was inhibited, SPC and thyroid transcription factor-1 ( TTF-1 ) expression levels were enhanced. After treatment with dexamethasone (DEX), 8-bromoadenosine 3′5′-cyclic monophosphate (8-Br-cAMP), 3-isobutyl-1-methylxanthine (IBMX), and keratinocyte growth factor (KGF), surfactant protein B and TTF-1 expression levels were enhanced. We found that A549-derived clones have plasticity in gene expression of alveolar epithelial differentiation markers and could be useful in studying ATII maintenance and differentiation.